ОСОБЕННОСТИ ЛЕЧЕНИЯ АРТЕРИАЛЬНОЙ ГИПЕРТЕНЗИИ У МУЖЧИН С ОПУХОЛЬЮ ПОЧКИ ПОСЛЕ ЛАПАРОСКОПИЧЕСКОЙ НЕФРЭКТОМИИ - С. С. Давыдова (Архивъ внутренней медицины)
Objective of the study is to analyze the dynamics of blood pressure in the early postoperative period in patients with a tumor of the kidney and hypertension after laparoscopic nephrectomy. Group for laparoscopic nephrectomy selected 53 patients with hypertension aged 37–65 years. Duration hypertension patients with kidney tumors was 6.5 ± 3.2 years. All patients to assess the effectiveness of the primary purpose or need antihypertensive therapy before the surgery was conducted ambulatory blood pressure monitoring, and with the purpose of correction of antihypertensive therapy after surgery blood pressure monitoring performed on the second and tenth day using the monitor МECG-DS-HC-01. Strengthening of antihypertensive therapy took all the patients on the second day after the operation, on the tenth day correction of antihypertensive therapy was needed 32 patients (60.4%). Once added to the treatment scheme nifedipineretard the decline of some indicators of blood pressure monitoring on the tenth day of the postoperative period. Further reception of antihypertensive drugs after surgery allowed to achieve the target values of blood pressure.